DISEMINASI INFORMASI ADMINISTRASI DAN AKADEMIK MELALUI KATALOG UNIVERSITAS TERBUKA PADA MAHASISWA PROGRAM NON PENDIDIKAN DASAR DI UPBJJ-UT MATARAM - Windi Baskoro Prihandoyo (CIVICUS : Pendidikan-Penelitian-Pengabdian Pendidikan Pancasila dan Kewarganegaraan, 2016)
Abstract:  This study aims to identify and analyze the effectiveness of Administrative and Academic Information Dissemination through the Open University Catalog On Non Basic Education Program Student in UPBJJ-UT Mataram. The method used in this research is descriptive correlational survey. The results in this study is that there was a significant relationship between: 1) the characteristics of the respondents, the accessibility of information and intensity of communication with the effectiveness of administrative and academic information dissemination through the catalog of the Open University in UPBJJ-UT Mataram. 2) Each of the three independent variables: characteristics, accessibility of information and communication intensity Non Basic student in UT UPBJJ Mataram. 3) Use of the Open University catalog with the catalog of benefits for Non Basic student in UT UPBJJ Mataram.